LEGAL CONSEQUENCES FOR OFFENDERS WHO VOTE MORE THAN ONCE IN THE CRIMINAL ACT OF THE GENERAL ELECTION (ELECTION) RULING STUDY NO. 132/PID.SUS/2019/PN.GST: AKIBAT HUKUM BAGI PELAKU YANG MEMBERIKAN SUARA LEBIH DARI SATU KALI DALAM TINDAK PIDANA PEMILIHAN UMUM (PEMILU) STUDI PUTUSAN NO. 132/PID.SUS/2019/PN.GST - Murtiyanto, Herlan (LPPM UPMI, 2023)
Article 156 of law Number 7 of 2017 concerning General Elections states that